COVID-19 Impact On English Language Teachers’ Professional Wellbeing: A Critical Review - KC , Rejina (Journal of NELTA, 2025)
The COVID-19 pandemic has brought significant challenges for educators, particularly English language teachers, whose professional and personal wellbeing have been affected in various ways. This review paper synthesizes empirical studies published between 2020 and 2022 to examine English language teachers’ wellbeing during the pandemic. For this, I have employed the Preferred Reporting Items for Systematic Review and Meta- Analysis (PRISMA) framework for critically analyzing the studies (n=30). I identified some key areas of professional challenges that include(a) increased workload, (b) lack of technological preparedness, (c) diminished social interactions; (d) lack of opportunities, for enhanced digital literacy and the development of innovative teaching methods; and (e) absence of effective coping strategies, including peer support, self-care routines, and institutional interventions. These findings can contribute to the broader conversation on teacher resilience by highlighting actionable insights for improving well-being through coping even in the crisis contexts like the pandemic. The existing literature has contributed as an evidence-based interventions by providing a deeper understanding of the unique challenges faced by English teachers. It is also highlighting the opportunities experienced by English teachers during the pandemic. The support and lesson learned can be an instrumental to build teacher resilience, ensuring their sustained effectiveness in navigating future challenges for their better personal and professional wellbeing.